PENGARUH PROMOSI KESEHATAN METODE PENYULUHAN TENTANG HIV/AIDS TERHADAP PENINGKATAN PENGETAHUAN REMAJA DI SMA N 5 PADANG - Sari Setiarini (Menara Ilmu, 2017)
Human Immunodeficiency Virus is a type of virus that attacks / infects white blood cells that cause the decline of human immune. Acquired Immune Deficiency Syndrome is a set of symptoms of the disease that arise due to the decrease in body immunity caused by HIV (Kemenkes RI, 2014). In 2014 (WHO) announced 36 million people worldwide suffered from HIV / AIDS and most of them live in poverty and in developing countries. Cases of HIV / AIDS in Indonesia from July to September recorded cases of HIV 7,335 cases, while AIDS cases 176 cases. The estimation and projection of the number of people with HIV / AIDS in low-risk female population increased from 190,349 cases in 2011 to 279,276 cases (0.10%) in 2016. The objective of the study was to investigate the effect of health promotion by extension methods on increasing adolescent knowledge about HIV / AIDS at SMA N 5 Padang in 2017.This research uses quasi ekperiment with pretest post test design in SMA N 5 Padang, population of 160 people, with sample 61 respondentsby cluster random sampling. The research with the questionnaire and counseling, then the data is processed by using wilcoxon test.From the statistical test of wilcoxon, p = 0,000 (p <0,05), it can be concluded that there is a significant effect on the improvement of knowledge before after being given counseling about HIV / AIDS in SMA 5 Padang in 2017.Suggestion for High School education institution N 5 Padang in order to improve the giving of wider material and giving counseling to all student in SMA Negeri 5 Padang about HIV / AIDS. As well as expected research can be developed by examining other factors of successful counseling about HIV / AIDS.